The Effect of Conflict Management and Work Environment on Employee Performance with Human Resource Management as a Mediating Variable - Lian, Cheng (STKIP Yapis Dompu, 2023)
The purpose of this study is to analysis how conflict management and work environment affects employee performance. This study also examine human resources management as a mediating variable. Analysis using 45 respondent who works with local and foreign company. This study using smartPLS as test kit and likert scale. The novelty of this study is human resources management has no role as a mediating variable. The evaluation of the model in this study used the evaluation of the outer model and inner model carried out with the help of smartPLS 4.0. Hypothesis testing was carried out with human resources management as a mediating variable, the relationship between the work environment and work performance was 0.491 while for conflict management with work performance was 0.033 where with these results the relationship became influential or could be said to be weakened. So it can be concluded that human resources management cannot mediate between latent variables.